RISK MITIGATION STRATEGY IN THE SNAKEFRUIT (Salacca zalacca) SUPPLY CHAIN: INTEGRATING FUZZY AND ANALYTICAL HIERARCHY PROCESS - Alfiyan, Anaam; Wahyudin, Moh; Guritno, Adi Djoko; Tsai, Kune-Muh (Fakultas Teknologi Pertanian Universitas Brawijaya, 2026)
Fruit supply chains, especially for extremely perishable goods like snakefruit (Salacca zalacca), are intrinsically vulnerable to challenges that might compromise the quality, safety, and economic value of these products after harvest. Prior research has identified various risks and associated mitigation strategies; however, these studies are often fragmented, focusing on risk identification, efficiency assessment, or qualitative recommendations, and fail to offer a cohesive framework that quantitatively assesses risks under uncertainty while systematically ranking mitigation strategies among supply chain participants. This study employs a Fuzzy logic to assess risk levels amid uncertainty via likelihood-severity evaluation and utilize the Analytical Hierarchy Process (AHP) to methodically prioritize mitigation strategies and essential stakeholders within a multi-actor supply chain context. Data was gathered via interviews with 196 participants engaged in the supply chain, comprising farmers, suppliers, distributors, agro-industrial enterprises, and retailers. The data were subsequently validated by experts to ensure accuracy. The findings indicate that the primary issues are pests and diseases, insufficient inventory, fluctuating pricing, declining quality, and uncertainty regarding demand levels. The processes occurring post-harvest, during transportation, and in response to market fluctuations are the most vulnerable as a result of this. A comprehensive analysis revealed that distributors are the primary actors, succeeded by suppliers. This underscores the significance of maintaining the supply chain and ensuring the product quality is maintained. To ensure safety, it is advantageous to adhere to good handling practices (GHP), enhance transportation efficiency, and refine quality control techniques